A Study on Accountability Language at the Level of the Primary School - (:unkn) unknown (KAMLA-RAJ ENTERPRISES, 2018)
The aim of this research is to reveal how teachers, principals, students, and parents think about and behave toward accountability issues in schools. Phenomenology, which is one of the qualitative research designs was used in the study. Data was collected from randomly selected teachers, principals, parents and students in randomly selected two state schools in Istanbul. Focus group interview was used as data collection method. Separately structured questionnaire was prepared for each group. While creating the questions, literature was reviewed and a pilot implementation was conducted to determine the validity. Data was analyzed through NVIVO 10. Parents hold teachers along with others responsible for learning of students, resolving problems that the students confront and to discipline school. Teachers take student expectations into consideration and accept that they are accountable to the students and parents. Teachers evaluate the role of parents and external stakeholders as threatening.
Keywords: Expectation; Leadership; Performativity; Responsibility; Stakeholder